Hydroxyapatite and montmorillonite filled high density polyethylene hybrid composites for biomedical applications - Husin, Muhamad Rasyidi (2012)
In this study, new composite formulation for biomedical applications was investigated. The effects of hydroxyapatite (HA) and montmorillonite (MMT) on the mechanical, morphological, thermal and biological properties of high density polyethylene (HDPE) composites which compatibilized with high density polyethylene grafted maleic anhydride (HDPE-g-MAH) were studied. These formulations were compounded using a single screw nano-mixer extruder followed by injection moulding. The effect of HA loadings up to 50 phr were studied and the compositions of MMT and HDPE-g-MAH were kept constant at 5 phr. The performance of the single screw nanomixer extruder was compared with a twin screw extruder. The mechanical properties were studied through tensile, flexural and izod impact testing. X-ray diffraction (XRD) was used to investigate the dispersibility of MMT layers. The thermal properties were analyzed using differential scanning calorimetry (DSC). The morphology of the composites were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The study of biological properties was carried out through bioactivity test using simulated body fluid (SBF) immersion. The morphology and calcium-phosphate (Ca-P) precipitation in SBF was characterized by SEM, accompanied by energy dispersive analysis x-ray (EDX) and XRD. The result showed that, the addition of HA significantly increased the strength and stiffness of composites but the elongation at break and impact strength were decreased. The HDPE-HA composites containing 50 phr of HA had the highest elastic modulus, tensile and flexural strength. However, with addition of MMT and HDPE-g-MAH, the composites containing 30 phr HA exhibited high tensile and flexural strength. The melting temperature (Tm) and crystallisation temperature (Tc) of the composite were not affected by the addition of HA particles, and the crystallinity of the HDPE matrix was increased with increasing of HA content. Incorporation of HA increased the thermal stability of the composites significantly. Based on the mechanical properties of the composite, the performance of single screw extruder nanomixer was more effective in enhancing the HA dispersion compared to twin screw extruder. The bulk formation of apatite layer covering at the composites surface indicated the excellent bioactivity properties of HA and depiction of bioactive composites. Results showed that the composite with 30 phr of HA had optimal mechanical and biological properties.